KEWENANGAN TNI ANGKATAN LAUT DALAM MELAKUKAN PENYIDIKAN TINDAK PIDANA ILLEGAL FISHING (Studi di Pangkalan TNI AL NIAS) - Putri Awin Susanti Zamili (Jurnal Panah Hukum, 2022)
Investigations into criminal acts of illegal fishing are carried out by Civil Servant Investigators, Police Investigators, and Navy Officers Investigators. With many agencies that have the authority, so that there is still overlapping authority in conducting investigations. Therefore, researchers are interested in conducting research on the authority of the Navy in conducting investigations into criminal acts of illegal fishing (study at the Nias Naval Base). The type of research used in this research is the type of sociological legal research. The research specification used is descriptive normative. The location of this research is the Nias Naval Base. The research time that will be used in this study is from February to March 2021. After all the data has been collected and systematically arranged, then it is analyzed using qualitative methods. Based on the research findings and discussion, it can be concluded that the Indonesian Navy in the context of law enforcement in the territorial waters of the Indonesian national jurisdiction has the authority to investigate illegal fishing crimes. As regulated in Article 73 of Law Number 45 of 2009 concerning Fisheries which stipulates that investigations of criminal acts in the field of fisheries in the management area of ​​the Republic of Indonesia are carried out by PPNS Investigators, Navy Officers Investigators, and/or Indonesian National Police Investigators. There is a need for strict regulatory changes regarding the granting of authority to investigate illegal fishing crimes. improving the quality of human resources of the Indonesian Navy investigators. Improving the quality of Indonesian Navy investigators through training, courses, and joint training to improve the professionalism and integrity of the investigators